Lichen planus—Peculiarities in children versus adults. A narrative review. - Chiriac, A.; Wollina, U. (European Journal of Pediatric Dermatology, 2024)
Lichen planus is a common pruritic, inflammatory skin disorder. A hallmark of the disease is Wickham’s striae. The disease occurs in all age groups but it has some noteworthy peculiarities during childhood. In children the incidence is 2-3%. In contrast to adult lichen planus, the pediatric type lacks a closer association to metabolic syndrome. Manifestations on the nail apparatus are less common in children. Oral lichen planus has no malignant potential in childhood. We present a review on peculiarities of pediatric lichen planus.